2017
DOI: 10.1007/s00246-017-1702-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Patent Ductus Arteriosus in Children with the Occlutech Duct Occluder

Abstract: The aim of this study was to evaluate the feasibility, efficacy and safety of transcatheter closure of patent ductus arteriosus (PDA) with the Occlutech duct occluder (ODO) in children. We reviewed the clinical records of 71 patients who underwent percutaneous closure of PDA with an ODO between September 2014 and August 2016. The Occlutech duct occluder was applied to 71 patients during the study period (September 2014-August 2016), and the results were analyzed in this study. Forty-two of the patients were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Occlutech 8/10 PDA occluder was used the most in 14 cases followed by Occlutech 6/8 PDA occluder in 11 patients. The operator preferred the use of Occlutech devices in most cases due to its low cost and easy availability in the regional market as well as high safety profile [ 13 ]. General anesthesia was given in 38 (74.5%) cases due to a higher number of younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Occlutech 8/10 PDA occluder was used the most in 14 cases followed by Occlutech 6/8 PDA occluder in 11 patients. The operator preferred the use of Occlutech devices in most cases due to its low cost and easy availability in the regional market as well as high safety profile [ 13 ]. General anesthesia was given in 38 (74.5%) cases due to a higher number of younger children.…”
Section: Discussionmentioning
confidence: 99%
“…The ODO is a self-expanding device that, according to its manufacturers, is designed to close PDA of various morphologies and has been successfully implanted even in hypertensive PDA [2][3][4][7][8][9][10][11] , manufactured with nitinol wire coated with titanium oxide containing PTFE patch inside; marketed for approximately eight years by the Occlutech company whose factories are in Germany and Turkey, in our country the devices of Turkish origin are the ones that arrive 12 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the ideal device for the closure of patent ductus arteriosus (PDA) does not exist due to the diversity of its morphologies and sizes 1 . The Occlutech® Duct Occluder (ODO) is a relatively new device on which there are some experiences [2][3][4][5][6][7][8][9][10] . Our objective is to communicate the deformity that an ODO device presented when it was delivered transcatheter.…”
Section: Introductionmentioning
confidence: 99%
“…The PDA occlusion using NOC did not show significant differences in the success rate according to the types of PDA, and it showed high success rates evenly in each group classified according to the The geometric shapes of PDA devices were developed since angiographic classification of PDA types was established by Krichenko A et al [11]. Some studies reported that the frequency order of PDA types, which consisted of mostly pediatric patients, was as follows: conical > elongated > tubular > window > complex or conical > tubular > elongated > window > complex [12,13]. Most studies reported that the conical type was the most common type of PDA, while the rarest one was the complex type.…”
Section: Discussionmentioning
confidence: 99%